Richard Wagner's Essays on Conducting : A New Translation with Critical Commentary. - Walton, Chris (Rochester : University of Rochester Press, 2021)
The first modern English edition of Richard Wagner's essays on conducting, extensively annotated, with a critical essay on Wagner as conductor: his aesthetic, practices, vocabulary, and impact.
Richard Wagner's Essays on Conducting -- Illustrations -- Acknowledgements -- Abbreviations -- Author's Note -- Introduction -- Reminiscences of Spontini -- Report on the Performance of Beethoven's Ninth Symphony in Dresden in 1846 -- About Conducting -- On Performing Beethoven's Ninth Symphony -- Richard Wagner and the Art of Conducting -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books